On a Casson Fluid Motion: Nonuniform Width Symmetric Channel and Peristaltic Flows - Simone Guadagni; Liviu Iulian Palade; Lorenzo Fusi; Angiolo Farina (Fluids, 2021)
Widely used for modeling biological fluids flows—in particular, blood vessel flows—a Casson flow is studied in a symmetric channel for which the aspect ratio enables one to use the lubrication approximation. Two flow driving conditions are prescribed: inlet–outlet pressure difference and peristaltic oscillations of the vessel walls. In both cases, starting from mass and momentum balance and using lubrication approximation, we investigate the conditions to be imposed on the driving mechanisms so that the inner plug does not come in touch with the walls. The study of the peristaltic flow is of great importance in view of its applications in physiology (including microcirculation applications).